Haplotype analysis and marker development of five salt-tolerant–related genes in rice (Oryza sativa L.) - Li, Pingbo; Li, Zhen; Liu, Xu; Zhang, Hua; Zhang, Shuyong; Liu, Fang; Li, Nana; Yang, Yongyi; Xie, Kun; Ding, Hanfeng; Yao, Fangyin (Frontiers in Plant Science, 2023)
Salinity stress is a great threat to the growth and productivity of crops, and development of salt-tolerant crops is of great necessity to ensure food security. Although a few genes with natural variations that confer salt tolerance at germination and seedling stage in rice have been cloned, effective intragenic markers for these genes are awaited to be developed, which hinder the use of these genes in genetic improvement of salt tolerance in rice. In this study, we firstly performed haplotype analysis of five rice salt-tolerant related genes using 38 rice accessions with reference genome and 4,726 rice germplasm accessions with imputed genotypes, and classified main haplotype groups and haplotypes. Subsequently, we identified unique variations for elite haplotypes reported in previous studies, and developed eleven effective intragenic makers. Finally, we conducted genotyping of 533 of 4,726 rice accessions from worldwide and 70 approved temperate geng/japonica (GJ) cultivars in China using developed markers. These results could provide effective donors and markers of salt-tolerant related genes, and thus could be of great use in genetic improvement of salt tolerance in rice.